Cover Image: Volume 45 Issue 6. Issue 6 (8th June 2022) - Scott, Colin; Lateef, Sundus S.; Hong, Christin G.; Dey, Amit K.; Manyak, Grigory A.; Patel, Nidhi H.; Zhou, Wunan; Sorokin, Alexander V.; Abdelrahman, Khaled; Uceda, Domingo; Teklu, Meron; Wu, Colin; et al.
Abstract : The cover image is based on the Full Article Inflammation, coronary plaque progression, and statin use: A secondary analysis of the Risk Stratification with Image Guidance of HMG CoA Reductase Inhibitor Therapy (RIGHT) study by Nehal N Mehta et al., https://doi.org/10.1002/clc.23808 .